A Theoretical Study of the Effect of Zr-, Nb-Doped and Vacancy-like Defects on H Desorption on MgH2 (110) Surface - German, Estefania (2014)
DFT calculations were used to study hydrogen desorption energy in a set of pure, Nb- or Zr-doped systems, containing vacancy-like defects and a MgH2 (110) defect-free surface. The preferential location site for dopants was determined by means of occupation energy analysis. Both transition metal atoms (Nb and Zr) preferred interstitial sites. The effect of vacancies in the systems was also considered. MgH2 with a Nb interstitial atom and MgH2 with a Zr interstitial atom containing a Mg vacancy modifies the surface geometry and weakens the Mg–H bonds thus easing the H desorption process.